Pembuatan Meja Bak Cuci Tangan Menggunakan Mutu Beton Sederhana dengan Memanfaatkan Limbah Olahan Rotan dan Sosialisasi Cuci Tangan 6 Langkah di Panti Asuhan Budi Mulya Kota Palangka Raya: Making a Handwashing Table Using Simple Quality Concrete Using Rattan Waste and 6 Steps Handwashing Socialization in Budi Mulya Orphanage Palangka Raya - Respati, Rida; Puspasari, Nirwana; Jaya, Hendra Putra; Silaban, Ridho Saleh; Permana, Ari Widya (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
The development of coronavirus or Covid-19 in Central Kalimantan is currently increasingly worrying. All areas in this province are now in red zone status. This transmission is very fast spreading, so we are doing outreach to the community at Budi Mulya Orphanage, Palangka Raya City, implementing 6 recommended handwashing steps to kill the Covid 19 virus that sticks to our fingers. Washing hands with soap is one of the sanitation measures to prevent disease. Even WHO also recommends 6 steps in washing the palms of hands, the palms of backs of hands, between the fingers, the backs of hands, the thumbs, and the tips of fingers. The last method of washing hands is to clean soap with running water and dry it. To support the 6-step handwashing program, we are working with the orphanage’s leadership to make a table for a water storage basin used for washing hands. The table is made permanent, made of reinforced concrete, whose composition of the reinforced concrete mixture is mixed with processed rattan waste that is no longer used as a substitute for concrete fiber. The rattan waste mixture used was 0.25% of the total volume of concrete.